PENGARUH FRONT SQUAT (METODE 5/3/1 JIM WENDLER) TERHADAP PENINGKATAN 1RM (ONE - REPETITION MAXIMUM) PADA ATLET ANGKAT BESI REMAJA DI PABSI JAMBI - Shalsabilla, Nazwa; Oktadinata, Alek; Hasibuan, Mhd. Usni Zamzami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Problem: When performing Cleans, junior athletes often fail to complete the end of the Clean, as is often the case with the inhibition of the standing position causing the barbell to fall. Therefore, to overcome these failures, it is necessary to exercise the strength of the legs that have a high transfer to the Clean movement, one of the most specific and effective exercises is the Front Squat, because the Front Squat movement resembles the position and technical demands of the standing phase in Clean. Objective: to determine the success of Jim Wendler's 5/3/1 method within 8 weeks, on the improvement of clean adolescent athletes. Methods: The study used a quantitative experiment with a One Group Pretest-Postest design. Results: Based on the results of the data study, it was found that p-value = 0.002 was smaller than 0.05. Thus H0 was rejected, thus proving that there is a significant influence of front squat exercises on the increase of 1RM clean in weightlifting adolescent athletes at PABSI Jambi. Conclusions: There was a significant effect of front squat exercises using Jim Wendler's 5/3/1 method on the improvement of 1RM clean in adolescent athletes. This increase is influenced by the training experience and the maturity level of the athlete. Same exercise program but different improvement due to physiological adaptation.